Comparative Study of Integrated Pest Management and Farmers Practices on Sustainable Environment in the Rice Ecosystem - Alam, Mohammad Zahangeer; Haque, Md. Manjurul; Islam, Md. Sirajul; Hossain, Emran; Hasan, Sabiha Binta; Hasan, Shahela Binte; Hossain, Md. Sakhawat (International Journal of Zoology, 2016)
Integrated pest management (IPM) is an environmentally friendly technology. IPM is a multifaceted approach to pest management that seeks to minimize negative impacts on the environment. This technique is an important step towards providing healthy, viable food for a growing global population. The focus of this study was to examine the impact of integrated pest management in a rice agroecosystem. Currently, more than 80% of farmers rely on pesticides. IPM methods employed in our study had an impact on the number of healthy tillers and hills and grain weight. The lowest percentage of dead heart (1.03) and white head (2.00) was found in the IPM treated plots. These plots had an average yield of 7.4 tonne/ha. We found that there were significant differences between the treatment and the observed percentage of dead heart, grain weight, and yield. We conclude that IPM practices are an effective strategy for obtaining high rice yields while protecting the environment and creating a more sustainable agroecosystem. Furthermore, the need for ongoing research and training on IPM methods will be essential for creating a sustainable rice agroecosystem.